Polyamines serum levels in episodic and chronic migraine. (1st February 2021) - Lionetto, Luana; Guglielmetti, Martina; Cipolla, Fabiola; Bernardini, Simone; Koehler, Bianca Emanuela; Capi, Matilde; De Bernardini, Donatella; Curto, Martina; Manetti, Roberto; Nicoletti, Ferdinando; Simmaco, Maurizio; Martelletti, Paolo
ABSTRACT: Background : Previous studies focused on food as the trigger of a migraine attack did not consider polyamines as possible activators and sensitizers of the trigeminal-vascular system through their interaction with NMDA glutamate receptors. Therefore, this study aimed to assess serum levels of nine polyamines and to evaluate their role as possible triggers and crisis maintainers in episodic and chronic migraine patients. Materials and methods : The study included 50 patients with episodic migraine (EM), 50 patients with chronic migraine (CM) and 50 healthy controls (HC). Serum levels of nine polyamines have been determined by Liquid Chromatography tandem Mass Spectrometry. Specifically, agmatine, spermidine, spermine, putrescine, cadaverine, arginine, ornithine, citrulline and lysine levels were studied. Results : Agmatine serum levels resulted reduced in EC patients with respect to CM and HC. Compared to HC subjects, serum levels of spermine and spermidine were statistically significantly increased both in CM and EM patients. Conclusions : The authors suggest that alterations of polyamines levels might contribute to the understanding of migraine external activation and help to clarify the potential role of NMDA receptor polyamines site antagonists in migraine treatment.